OF PRINCES AND PROMISES - Menon, Sandhya (New York : Somin & Schuster, 2021)
Caterina LaValle is determined to show she's still the queen of St. Rosetta's Academy. Sure, her crown may be slightly askew after her ex-boyfriend, Alaric, cheated on her, but she's a LaValle. She'll find a way to march right back in there, her hands clutching the strings to the whole puppet show. This time, she's going to be untouchable. Rahul Chopra knows that moment he shared with Caterina LaValle at the winter formal meant something. Surely she feels it, too. He's a little uncertain how someone like him (socially inept to a point way past "adorkable") could fit into her world, but he's loved Caterina for years. He knows they'll find a way. When Caterina finds out Alaric is taking a supermodel to the upcoming gala, she knows she cannot arrive without the perfect date. But the thought of taking another superficial St. R's boy exhausts her. The solution? Sweet-but-clueless Rahul Chopra and a mysterious pot of hair gel with the power to alter the wearer into whatever his heart desires. When Rahul tries it, he transforms instantly into RC -- debonair, handsome, and charming. But transformation comes with a price: As Rahul enjoys his new social standing, the line between his two personas begins to blur. Will he give up everything, including Caterina, to remain RC? Or will this unlikely pair find their way back to each other?
Keywords: Self-actualization (Psychology) -- Fiction; Love -- Fiction; Interpersonal relations in adolescence -- Fiction; Romance fiction; Young adult fiction